Critical and Creative Thinking for Learning Effectiveness in the Digital Era in Developing ASEAN Countries - Ramadhani, Undari; Zirmansyah, Zirmansyah; Ushuluddin, Achmad; Kamaludin, Faisal Sundani (Psikoborneo: Jurnal Ilmiah Psikologi, 2026)
The digital transformation in higher education has intensified the need for learners to develop advanced cognitive skills, particularly critical and creative thinking, to achieve optimal learning outcomes. This study aims to synthesize empirical and theoretical research published between 2020 and 2025 that examines the relationship between critical and creative thinking and learning effectiveness in digital environments within developing ASEAN countries. Using a systematic literature review guided by the PRISMA framework, ten journal articles were selected from Scopus, ERIC, DOAJ, Google Scholar, and Garuda databases. The studies reveal that integrating critical and creative thinking enhances student engagement, problem-solving, and adaptability in technology-mediated postgraduate learning. However, disparities in digital access and pedagogical design remain significant challenges across developing ASEAN contexts. The findings highlight the importance of metacognitive regulation, collaborative learning, and innovative instructional strategies grounded in educational psychology to strengthen postgraduate learning outcomes. This review contributes to understanding how higher-order thinking skills operate in developing ASEAN educational contexts and offers recommendations for future research and the development of digital pedagogy. This is an open-access article under the CC–BY-SA license.Transformasi digital dalam pendidikan tinggi telah meningkatkan kebutuhan peserta didik untuk mengembangkan keterampilan kognitif tingkat lanjut, khususnya berpikir kritis dan kreatif, guna mencapai hasil belajar yang optimal. Penelitian ini bertujuan untuk mensintesis penelitian empiris dan teoretis yang dipublikasikan antara tahun 2020 hingga 2025 mengenai hubungan antara berpikir kritis dan kreatif dengan efektivitas pembelajaran di lingkungan digital pada negara-negara ASEAN berkembang. Menggunakan systematic literature review yang dipandu oleh kerangka PRISMA, sepuluh artikel jurnal dipilih dari basis data Scopus, ERIC, DOAJ, Google Scholar, dan Garuda. Hasil penelitian menunjukkan bahwa integrasi kemampuan berpikir kritis dan kreatif mampu meningkatkan keterlibatan mahasiswa, kemampuan pemecahan masalah, serta adaptabilitas dalam pembelajaran pascasarjana berbasis teknologi. Namun demikian, kesenjangan akses digital dan desain pedagogis masih menjadi tantangan utama di berbagai konteks negara ASEAN berkembang. Temuan penelitian menegaskan pentingnya regulasi metakognitif, pembelajaran kolaboratif, dan strategi pembelajaran inovatif yang berlandaskan psikologi pendidikan untuk memperkuat hasil belajar pascasarjana. Tinjauan ini berkontribusi dalam memahami bagaimana keterampilan berpikir tingkat tinggi berperan dalam konteks pendidikan negara ASEAN berkembang serta memberikan rekomendasi bagi penelitian selanjutnya dan pengembangan pedagogi digital. Artikel ini merupakan artikel akses terbuka di bawah lisensi CC–BY-SA.